Smarteye.id’s Business Expansion Strategy for Global Market Penetration through the Ansoff Matrix - Sufyandi Aditiya; Kirana, Desty Hapsari Kirana (CV Putra Publisher, 2025)
The rapid advancement of Virtual Reality (VR) technology has spurred demand for high-quality VR content, but its development remains time-consuming and costly. Smarteye.id, an Indonesian tech start-up backed by Telkom Indonesia, addresses this challenge with Seville, a VR plugin designed to streamline content creation. With global VR adoption on the rise, Smarteye.id aims to expand Seville internationally. However, this expansion faces challenges such as fierce competition, varying consumer preferences, and product localization constraints. This study applies the Ansoff Matrix to identify potential strategies for global market entry, from new product development to market penetration. Findings suggest that a product development strategy offers a comprehensive approach to accelerating Smarteye.id's growth. The research contributes to strategic management and technology marketing fields.